Dampak Pelanggaran Etika Iklan Minuman Gratis Holywings di Sosial Media Instagram Tahun 2022 - Maretha Azzuhriyah; Agus Hermanto (Lembaga Pengembangan Kinerja Dosen, 2024)
The use of social media does provide many positive benefits, especially Instagram, but it does not rule out the possibility that there are also a number of negative impacts such as ethical violations by using this platform to spread hoaxes, slander, insults, insults and so on. other harsh language, even to the point of being used for free advertising. . For this reason, all advertisers must uphold the Advertising Ethics that have been established in a guideline, namely the Indonesian Advertising Ethics (EPI). Indonesian Advertising Ethics (EPI) functions as a guideline for advertising in Indonesia, as well as a guideline in discussing these issues. One of the Instagram posts made by Holywings was the subject of qualitative research using content analysis techniques this time. The aim of this research is to determine the form of advertising for Holywings free drinks, what violations Holywings has committed, and the impact caused by Holywings' violations of advertising ethics on Instagram. The results obtained from this research are that there are ethical violations in advertising on Instagram social media carried out by Holywings, including violations involving content that offends SARA and illegal content. So that the impact of advertising ethics violations committed by Holywings can be studied.